Pengaruh Status Sosial Ekonomi Orang Tua Dan Motivasi Belajar Terhadap Prestasi Belajar Kimia Siswa SMA Negeri Di Kabupaten Konawe - Mukhlis, Rasniaty; Dahlan, Dahlan; Ahmad, La Ode (Jurnal Penelitian Pendidikan Fisika, 2020)
This research aims to examine and analyze: (1) the influence of parents' socio-economic status on chemistry learning achievement, (2) the effect of learning motivation on chemistry learning achievement, (3) differences in motivation for learning coastal students with students in Watershed, (4) differences in learning achievement of coastal students with students in Watersheds. The location of this research is the SMAN in Konawe District. This type of research is associative research and data collection tools use questionnaires and student learning outcomes report cards. The population is 385 students. Sampling was done by proportional random sampling technique, with a sample of 193 people. Data analysis techniques used descriptive analysis and multiple regression. The results showed: (1) parents' socio-economic status towards chemistry learning achievement by 18%; (2) learning motivation towards chemistry learning achievement by 29%; (3) there are differences in motivation to learn coastal students with students in Watersheds, (4) there are differences in learning achievement of coastal students with students in Watersheds. Based on the results of this study, it was concluded that parents' socio-economic status and motivation had an influence on the high school chemistry learning achievement in Konawe District.